SISTEM INFORMASI MANAJEMEN PENJUALAN AAM CELL - Arif Maulana Ade Putra; Dedy Irfan (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
Aam Cell's management information system aims to provide convenience in customer serving, selling, stock reporting and financial reporting. The selling process is doing by  online system on the web, so customers do not need to the counter to buy the goods. This selling information system is designed using Unified Modeling Language (UML) and Waterfall design method. The proposed design system is described in four UML stages, they are context diagrams, use case diagrams, Activity  Diagrams and class diagrams. While the waterfall design method through the process of planning, modeling, construction, and deployment, which results in continuous support for a complete software. The tools used in developing this system are the PHP (Hypertext Preprocessor) programming language with the Laravel framework, JavaScript, and using the MYSQL database. The security techniques used in designing this system are encryption, session and restrictions on the access rights of each user. With this system, it would be expected to assist customers in buying goods online, can help counter owners in managing goods stock and counter finance, so that the counter owner can estimate the profit correctly.Keywords: Management Information System, Counter, PHP, Laravel, MySQL.